2017
DOI: 10.1177/1947603517710308
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Regeneration in Full-Thickness Patellar Chondral Defects Treated with Particulated Juvenile Articular Allograft Cartilage: An MRI Analysis

Abstract: Background. Full-thickness cartilage lesions of the patella represent a common source of pain and dysfunction. Previously reported surgical treatment options include marrow stimulation, cell-based treatments, and osteochondral transfer. Minced juvenile allograft cartilage is a novel treatment option that allows for a single stage approach for these lesions. Hypothesis. Particulated juvenile allograft cartilage (PJAC) for the treatment of chondral defects of the patella would offer acceptable lesion fill rates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…There is a limited body of literature reporting clinical outcomes for particulated juvenile allograft transplantation. However, several authors demonstrated favorable results in patients with focal chondral lesions on the patella and trochlea [ 44 •, 45 •, 103 ], with good to excellent defect fill in short and mid-term results [ 45 •, 104 •]. Particulated juvenile articular cartilage has also been found to produce a mixture of hyaline and fibrocartilage with a dominance of type II collagen after 2 years follow-up [ 45 •] (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a limited body of literature reporting clinical outcomes for particulated juvenile allograft transplantation. However, several authors demonstrated favorable results in patients with focal chondral lesions on the patella and trochlea [ 44 •, 45 •, 103 ], with good to excellent defect fill in short and mid-term results [ 45 •, 104 •]. Particulated juvenile articular cartilage has also been found to produce a mixture of hyaline and fibrocartilage with a dominance of type II collagen after 2 years follow-up [ 45 •] (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the IKDC all techniques showed superior final follow-up absolute scores compared with ACI. Improvement in at least 1 score was present in all but 6 studies (2 only had magnetic resonance imaging [MRI] results 21,59 and 4 only reported follow-up scores 28,41,49,50 ) and 32 studies reported a significant improvement in at least 1 score. Generally, all techniques achieved and surpassed the MCID threshold reported in the literature.…”
Section: Postoperative Clinical and Functional Outcome Measuresmentioning
confidence: 99%
“…38 PJAC MRI outcomes were reported in 4 studies (n = 90 of the 102 patients included) achieved a reasonable defect fill (>33%) in more than half of the patients and very good (>67%) in 56% to 90% of the patients, with graft hypertrophy rates ranging from 0% to 33% of patients. 21,[41][42][43] Subchondral marrow changes were frequently reported (range, 0% to 90%) 21,[41][42][43] as well as synovitis (range, 0% to 58), 21,41,42 but low rates of graft displacement were noted (range, 3% to 7%). 21,42 T2 mapping technique was performed in 3 studies (n = 75) and revealed prolonged mean T2 relaxation time at the graft site at both the deep and superficial zone compared with adjacent normal cartilage, 21,42,43 but this difference improved (decreased) overtime.…”
Section: Imaging Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the characteristics of strong proliferation of transplanted juvenile cartilage, particulated juvenile allograft cartilage (PJAC) from donors under 13 years old is prepared and stored at low temperature, and then applied with brin glue to the cartilage defects [9]. At present, DeNovo NT, a commercial product of PJAC, has been widely used in clinical practice and has achieved satisfactory therapeutic effects [10][11][12][13][14][15]. Compared with microfractures and ACC, PJAC transplantation has better long-term e cacy.…”
Section: Introductionmentioning
confidence: 99%